The Possible Effects on Socio-Economic Inequalities of Introducing HPV Testing as Primary Test in Cervical Cancer Screening Programs - Giorgi Rossi, Paolo; Baldacchini, Flavia; Ronco, Guglielmo (Frontiers in Oncology, 2014)
Background HPV-test is more effective than Pap test in preventing cervical cancer. HPV-based screening will imply longer intervals and a triage test for HPV positive women. It will also permit the use of self-sampling devices. These innovations may affect population coverage, participation, and compliance to protocols, and likely in a different way for less educated, poorer, and disadvantaged women. Aim To describe the impact on inequalities, actual or presumed, of the introduction of HPV-based screening. Methods The putative HPV-based screening algorithm has been analysed to identify critical points for inequalities. A systematic review of the literature has been conducted searching PubMed on HPV screening coverage, participation, and compliance. Results were summarised in a narrative synthesis. Results Knowledge about HPV and cervical cancer was lower in women with low Socio-economic status and in disadvantaged groups. A correct communication can reduce differences. Longer intervals will make it easier to achieve high-population coverage, but higher cost of the test in private providers could reduce the use of opportunistic screening by disadvantaged women. There are some evidences that inviting for HPV test instead of Pap increases participation, but there are no data on social differences. Self-sampling devices are effective in increasing participation and coverage. Some studies showed that the acceptability of self-sampling is higher in more educated women, but there is also an effect on hard-to-reach women. Communication of HPV positivity may increase anxiety and impact on sexual behaviours, the effect is stronger in low educated and disadvantaged women. Many studies found indirect evidence that unvaccinated women are or will be more probably under-screened. Conclusions The introduction of HPV test may increase population coverage, but non-compliance to protocols and interaction with opportunistic screening can increase existing inequalities.